MORAL VALUE IN ONE PIECE ANIME MOVIE OF CHOPPER PLUS BLOOM IN THE WINTER - Hastuti, Hilda; Dewi, Puspita (Humanitatis : Journal of Language and Literature, 2020)
This research aims to describe moral value in One Piece Anime Movie of Chopper Plus Bloom in The Winter created by Eiichiro Oda. The researchers obtained the data from the movie Video through watching, screenshot the video and copied the every single of scene in the movie video. Researchers took data only the appropriate the data which contained the moral value. The method used of this research was descriptive analysis method. The result of the research found that moral value was intrinsic moral value and three types of moral values that were the issue of human relationship with themselves, the human relationship with others, and relationship with God. Three types of those moral values shown (1) Chopper couldn’t accepted by others and It was shot by inhabitants (2) Luffy as a captain of the straw hat Pirate crew took responsibility to his crew by taking care of his crew (3) Chopper was considered as disgrace of his family because chopper has got blue nose and he was isolated by others and he found his the first friend dr Hiluluk as a form gratitude. Keywords: Anime, moral values, one piece